Two Late New Kingdom or Early Third Intermediate Period Hieratic Graffiti in the Temple of Khonsu at Karnak - Jasnow, Richard.
This article examines two hieratic graffiti found in the Temple of Khonsu at Karnak during the ARCE Conservation Project. The texts probably date to the end of the Twentieth Dynasty up to the beginning of the Twenty-first Dynasty. A translation with commentary is supplemented by photographs and digital facsimiles of the individual texts.